2018
DOI: 10.2217/fmb-2018-0066
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Modulated Virulence Factors of Entamoeba Histolytica

Abstract: Entamoeba histolytica is a human parasite that causes amoebiasis, a disease that affects the colon and liver and is prevalent worldwide. This protozoan requires a high concentration of iron to survive and reproduce. Iron modulates the expression of parasite virulence factors, including hemoglobinases, hemoglobin-binding proteins and cysteine proteases, as well as proteins related to the amoebic cytoskeleton. This review summarizes the virulence factors that are affected by iron, resulting in upregulation or do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…To determine the effect of iron, growth kinetics were carried out at different iron concentrations. We observed a drastic reduction in the number of Giardia trophozoites without iron supplementation, which indicates that this parasite requires this metal in order to grow; this also occurs in other pathogens [ 18 , 21 , 26 , 28 , 47 , 48 , 49 ]. It would be interesting to study iron chelation as a chemotherapeutic alternative in Giardia growth under different iron conditions.…”
Section: Discussionmentioning
confidence: 70%
“…To determine the effect of iron, growth kinetics were carried out at different iron concentrations. We observed a drastic reduction in the number of Giardia trophozoites without iron supplementation, which indicates that this parasite requires this metal in order to grow; this also occurs in other pathogens [ 18 , 21 , 26 , 28 , 47 , 48 , 49 ]. It would be interesting to study iron chelation as a chemotherapeutic alternative in Giardia growth under different iron conditions.…”
Section: Discussionmentioning
confidence: 70%
“…Iron is an essential trace-metal for all organisms and it is a well-known regulator of virulence genes in many pathogenic bacteria (Begg, 2019) but also in pathogenic protozoa, including Entamoeba histolytica, Trichomonas vaginalis, Trypanosoma, and Leishmania (Niu et al, 2016;Gastelum-Martínez et al, 2018;Paiva et al, 2018). This is because iron is an essential constituent of many proteins in the pathogens, including metabolic and antioxidant enzymes and virulence factors (Arroyo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The observed effects of iron on the expression of a small set of HCMPs and the fact the iron is a well-known regulator of virulence in intestinal bacteria (Begg, 2019) and protozoa (Gastelum-Martínez et al, 2018) inspired us to study the effects of iron on the total Giardia transcriptome. RNA Sequencing was performed on trophozoites grown in media with different levels of free iron to assess global changes in gene expression.…”
Section: Giardia Responses To Iron Depletionmentioning
confidence: 99%
“…Furthermore, if the accompanying bacterial flora is eliminated, the virulence of E. histolytica decreases rapidly; therefore, some strains that have been grown axenically for many years have lost their pathogenicity (Bos and Van de Griend, 1977; Costa et al ., 2006). Moreover, it has been suggested that nutritional modifications may alter the motility, and expression of the virulence factors for this parasite (Marie and Petri, 2014; Gastelum-Martínez et al ., 2018). The objective of the current study was to evaluate the impact of vitamin supplementation on the pathogenicity of E. histolytica grown axenically.…”
Section: Introductionmentioning
confidence: 99%